Can tiny houses on wheels comply with Australian housing provisions?. Issue 3 (2nd October 2018) - Strachan, Janine Heather
ABSTRACT: Tiny houses on wheels (THOW) are gaining significant interest and momentum in Australia, as they offer alternative housing to the traditional housing model. A significant challenge for the acceptance of THOW relates to ambiguity on how they should be treated under regulations. The construction of THOW straddle both caravan regulations and housing regulations, which can raise significant debate in the tiny house sector, and a review of the National Construction Code Volume 2, Housing Provisions reviews how a THOW could be constructed to include the key elements of the Housing Provisions, or where dispensation maybe sought.